Divine dwellers in the desert - Mallik, Gurdial (Bombay : Nalanda Publications, 1949)
Based on lectures delivered during 1932-33 at Visvabharati, Santiniketan, on the mystics of Sindh, Pakistan.
Master microform held by: ICRL.
0
Keywords: MCE; Sufism -- Pakistan -- Sindh